Xanthones from root barks of garcinia mangostana / Nurin Nadiah Abdul Halim - Abdul Halim, Nurin Nadiah (2019)
Mangosteen fruit was widely used as medical purpose such as medicine to treat abdominal pain, diarrhea and infected wound. This was due to the presences of active compounds such as xanthones. Hence, root barks of Garcinia mangostana was chosen for further analysis. Detailed study on the cold extraction of ethyl acetate extract from root barks of Garcinia mangostana have resulted on the isolation of three compounds, which is α-mangostin (15), mangosharin (42) and 1,6-dihydroxy-3,7-dimethoxy-2-(3-methylbut-2-enyl)-xanthone (41). The structure of these compounds were identified and elucidated by using spectroscopy methods such as 1H NMR, 13C NMR, infrared (IR), and EIMS.